2021
DOI: 10.1016/j.jtho.2021.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A Tuft Cell–Like Signature Is Highly Prevalent in Thymic Squamous Cell Carcinoma and Delineates New Molecular Subsets Among the Major Lung Cancer Histotypes

Abstract: Introduction: In-depth genomic characterization of thymic epithelial tumors (TETs), comprising thymomas and thymic carcinomas (TCs), failed to identify targetable mutations and suggested unique biology of TETs, including KIT expression in most TCs. Recently, tuft cell-like medullary thymic epithelial cells were identified in the murine thymus, and our reanalysis of the published gene expression data revealed that these cells express KIT. In addition, recently, a minor subset of SCLCs with tuft cell-like featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
82
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(100 citation statements)
references
References 45 publications
(93 reference statements)
15
82
1
Order By: Relevance
“…Since gender and WHO histotype distribution as well as GTF2I mutation rates were similar in the Indian and German cohort and in line with a previous world-wide study ( 6 ), racial-ethnic, environmental and lifestyle factors appear not to have a major impact on the molecular mechanism(s) driving the development of thymomas. A similar conclusion was recently drawn in relation to thymic squamous cell carcinomas in which age-related rather than racial-ethnic and environmental factors appear to be related to oncogenesis (6 , 21) .…”
Section: Discussionsupporting
confidence: 79%
“…Since gender and WHO histotype distribution as well as GTF2I mutation rates were similar in the Indian and German cohort and in line with a previous world-wide study ( 6 ), racial-ethnic, environmental and lifestyle factors appear not to have a major impact on the molecular mechanism(s) driving the development of thymomas. A similar conclusion was recently drawn in relation to thymic squamous cell carcinomas in which age-related rather than racial-ethnic and environmental factors appear to be related to oncogenesis (6 , 21) .…”
Section: Discussionsupporting
confidence: 79%
“…JASPAR analysis revealed that POU2F3 carries 6 putative SOX9-binding sites along its DNA transcriptional regulatory region, with a homology higher than 80% (Supplementary Table 7). In addition, SOX9 expression was positively associated with the expressions of TRPM5, which is required for the function of thymic tuft cells, and KIT, which is frequently expressed in thymic carcinomas (Figure 3E) (25,28). Moreover, we observed that SOX9 was correlated with almost all members of the TAS2R family (Figure 4) which are overexpressed in thymic tuft cells (25).…”
Section: Sox9 Was Correlated With Genes Associated With the Thymic Tuft Cells Phenotype In Thymomamentioning
confidence: 72%
“…In thymomas, we found that SOX9 expression was positively correlated with the expression of HIPK2, which is a critical transcriptional factor determining thymic tuft cells development and shaping thymic function (25). POU2F3, which is required for the development and function of thymic tuft cells, was found to be highly expressed in thymic squamous cell carcinomas (25,28). By JASPAR analysis, we found that POU2F3 might be a target of SOX9.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the thymus, tuft cells help shape the microenvironment and influence innate immunity [48][49][50]. Molecular analysis using public databases and frozen tissues revealed that POU2F3 and GFI1B, both tuft cell-related genes, are highly expressed in thymic squamous cell carcinoma [51]. In addition, the authors assessed the KIT expression status; POU2F3 expression was strongly correlated with KIT expression, suggesting that POU2F3 may drive KIT expression.…”
Section: The Biology Of Thymic Carcinomamentioning
confidence: 99%